Critical Thinking Ability Improvement: The Impact of STAD Learning Model in Mathematic Courses - Wibowo, Dodiet Enggar; Mustadi, Ali; Muanifah, Mahmudah Titi (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
According to some studies on school student, the application of the STAD method in some subject can improve critical thinking ability. However, according to other studies, STAD in some subject for school students cannot improve critical thinking ability. This study, hence, aims to discover the impact of the application of STAD in improving critical thinking ability, especially in mathematics course for university students. The experiment was carried out in a quasi-experimental design, especially the pretest-posttest non-equivalent group type. The findings of this study indicate that the application of STAD in mathematics learning can improve critical thinking ability. The advantages of using STAD can be seen from the increase in critical thinking ability, both abilities in the low, medium, and high categories. This study also confirms the findings of other studies that the application of cooperative and problem-based learning methods is effective in improving critical thinking ability. However, in contrast to other studies that reveal the benefits of STAD can be obtained after a long time of application (9 weeks - 8 months), this study shows that the benefits of STAD can be obtained in a relatively short time. This occurs because the treatment in the experimental class meets the criteria set by the experts, and uses three important structures proposed by experts, too. This research, therefore, has implications for the need to use problem-based cooperative learning methods.